Żydowskie modele historiograficzno-egzegetyczne doby hellenistycznej w kontekście aktywności literackiej diaspory aleksandryjskiej - Siwek, Krzysztof (Warszawskie Studia Teologiczne, 2018)
The expression of Jewish identity in national and political terms is found in a wide range of writings and literary genres. The form which lent itself most readily to this purpose was undoubtedly history writing. History, as the story of the people’s past and origin, had always been highly valued in Judaism. Much of the biblical material has a “history-like” character in the sense that it tells the story of the people within a chronological framework. In the Hellenistic age the Jews had a new reason to retell the story of their past. The spread of Hellenism under Alexander the Great and his successors was accompanied, at least initially, by considerable Greek curiosity about the strange peoples of the East. A number of writers, such as Hecataeus of Abdera, Demetrius, Artapanus, Pseudo-Hecataeus and Eupolemus, attempted to satisfy it. They did express themselves in forms which might have been accessible to the Greeks.We may distinguish three main approaches to the past in the Jewish Hellenistic literature: the Septuagint as an example of religion work, chronicles and the historical romances, the epic and philosophical poets.